Disequilibrium and divinity salience as invariant structures in the halal executives’ experience of eudaimonia / Jalilah Ahmad, Rosmimah Mohd. Roslin and Mohd. Ali Bahari Abdul Kadir. - Ahmad, Jalilah; Mohd. Roslin, Rosmimah; Abdul Kadir, Mohd. Ali Bahari (Universiti Teknologi MARA Cawangan Selangor, 2019)
The global Halal industry is large and continues to grow as the global Muslim population increases in size and dispersion. There are 1.84 billion Muslims today spread over 200 countries and is expected to increase to 2.2 billion by 2030. The industry will be worth USD6.4 trillion by the end of 2018 with more non-traditional players and emergent markets. The stakes are high with pressures to generate novel and sustainable practices. This goes beyond systems and hard skills as it needs to cut into the self – the person of virtues in virtuous acts, not because they “have to” but because it is the purpose of humankind or his telos - to be “living well” and “acting well” or eudaimonia. This study seek to explore Halal executives’ lived experience of “eudaimonia.”. Using Giorgi’s descriptive psychological phenomenological method for data analysis, the study elicits two distinct invariant structures – ‘disequilibrium in status quo’ and ‘divinity salience’.